2011
DOI: 10.3892/etm.2011.264
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications and characteristics of factor forkhead box protein 3 in gastric cancer

Abstract: Abstract. Transcription factor forkhead box protein 3 (FOXP3) is a specific marker of naturally occurring regulatory T cells (Tregs). Recently, various reports have suggested that FOXP3 may represent a tumor escape mechanism in cancer cells apart from its roles in Tregs. In the present study, the clinical and biological characteristics of FOXP3 were evaluated in human gastric cancer. The expression and localization of FOXP3 in gastric cancer cell lines was analyzed to evaluate its cellular biological features.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(25 reference statements)
2
2
0
Order By: Relevance
“…We also observed FOXP3 expression in both GC and para-carcinoma tissues. Expression of FOXP3 in GC tissues was higher as compared to that in para-carcinoma tissues, which was consistent with previous studies [31, 35]. Additionally, expression levels of FOXP3 was associated with pathological grading of GC, which was also consistent with results from a previous study by Jiang et al [35].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We also observed FOXP3 expression in both GC and para-carcinoma tissues. Expression of FOXP3 in GC tissues was higher as compared to that in para-carcinoma tissues, which was consistent with previous studies [31, 35]. Additionally, expression levels of FOXP3 was associated with pathological grading of GC, which was also consistent with results from a previous study by Jiang et al [35].…”
Section: Discussionsupporting
confidence: 82%
“…Expression of FOXP3 in GC tissues was higher as compared to that in para-carcinoma tissues, which was consistent with previous studies [31, 35]. Additionally, expression levels of FOXP3 was associated with pathological grading of GC, which was also consistent with results from a previous study by Jiang et al [35]. This suggested that FOXP3 expression is associated with the degree of GC differentiation, No correlation was found between FOXP3 expression and lymph node metastasis in our study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…FOXP3+Tregs are reported to be closely related to the incidence and development of GC, and increase FOXP3+Tregs infiltration in GC tissues can predict poor prognosis ( 55 ). FOXP3, a key protein in Treg differentiation and function, may influence tumor differentiation and immune escape in GC patients ( 56 ). In this study, we found that PGR expression was positively related to markers of Tregs, such as FOXP3, CCR8, STAT5B, and TGFB1 ( Tables 2,3 ).…”
Section: Discussionmentioning
confidence: 99%